Factors Correlated with Stress of Patients with Diabetes Mellitus Type 2 in Princess Maha Chakri Sirindhorn Medical Center, Ongkharak, Nakhonnayok Province - ไผ่ตระกูล จารุวรรณ; รัศมีพงศ์ ศรีสุดา; พันธ์สวัสดิ์ กวินนา; พิมตะครอง สุนัฐนันท์; นรภาร เบญจรัตน์; สิริวิริยะพัฒน์ ภัทรภา; เกนการณ์ มะปราง; สำราญบำรุง วิภาวรรณ; วัฒนปัญญาสกุล รัตนภูมิ (Nursing Journal of The Ministry of Public Health, 2019)
This study was conducted to investigate the factors correlated with stress among patients with diabetes mellitus type 2. A cross-sectional descriptive design was used in this study. A convenience sampling technique was used to recruit 163 Diabetes Mellitus type 2 patients from the outpatient department of HRH Princess Maha Chakri Sirindhorn Medical Center, Ongkharak, Nakhonnayok Province. The tools used for data collection included 1) a questionnaire regarding general information about diabetes, 2) a Diabetic coping behaviors questionnaire, and 3) a Self-analysis stress test evaluation questionnaire. Data analysis was carried out using the SPSS program to obtain the frequency, percentage, Pearson correlation coefficient and spearman rank correlation coefficient. The main findings found that more than half of the respondents had a normal level of stress coping (57.1%) and low stress (55.8%). Factors that affect the level of stress were: 1) blood sugar has positive significant correlation with stress (rp=.16, p=.04), which means that the blood glucose level varies with the stress level, 2) coping has negative significant correlation with stress (rs=-.24, p=.01), which means coping with stress was inversely related with stress level. The results of this study can be used as basic information for the design and development of programs to solve stress problems in diabetic patients. The emphasis should be on the importance of reducing blood sugar levels and further enhancing patients’ ability to cope with stress.